Development of quality standards of Alpinia galanga (Linn.) Willd. Rhizome - Humaira Farooqi3, Showkat R. Mir2, Mohammad Yusuf2; Hamid Nawaz Khan2, Parwaiz Akhtar1, Mohd Ali2, M.P Sharma4 (Current Botany, 2010)
<span style="font-family: Byington; font-size: 8pt; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Alpinia galanga<span style="font-family: Byington; font-size: 8pt; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> (Linn.) Willd. belonging to family Zingiberaceae is a perennial herb bearing rhizomes growing throughout the Eastern Himalayas and South West India. It is herbal medicine of day to day life. In present investigation an attempt has been made for the pharmacognostical standardization and evaluation of A. galanga rhizome. The pharmacognostical evaluation comprises of detailed macroscopy, powdered microscopy, fluorescence analysis and physical constants such as ash and extractive values. The rhizome extracts were subjected to preliminary phytochemical screening. The data obtained in present study will serve as valuable tool for identification, authentication and detection of adulterants, standardization and quality control of the drug. The developed technique will also be useful for the standardization of formulations containing A. galanga.